Hongos fitopatógenos que infestan las plantas ornamentales del campus Universitario de la Facultad de Ciencias Biológicas – UNAP - Massari Repetto, Valeria (2025)
This study was conducted on the university campus of the Faculty of Biological Sciences – UNAP, with the objective of evaluating the phytopathogenic fungi that infest ornamental plants. To achieve this, 36 samples of leaves and stems from ornamental plants showing visible signs of spots, necrosis, and wilting were collected and processed in the Mycology Laboratory of the Faculty of Biological Sciences. The samples were cultured on Potato Dextrose Agar and in a humid chamber for the isolation and microscopic identification of the fungi. A total of ten genera and/or species of phytopathogenic fungi were identified. The most frequently detected were Fusarium sp. (30%) and Aspergillus sp. (26%), followed by sterile mycelial structures (10%), all of which showed very high infestation levels. Cylindrocladium sp. followed with a relative frequency of 6%. Lastly, fungi with low incidence (2.5%) included Penicillium sp., Fusarium oxysporum, Monotospora sp., Paecilomyces lilacinus, Mucor sp., and Fusarium solani. Regarding the variation of temperature and humidity in relation to infestation frequency, it was observed that as temperature increases, infestation frequency tends to decrease, suggesting that higher ambient temperatures may hinder the development and infestation of phytopathogenic fungi species (Spearman’s correlation = 0.07, p ≤ 1.0). In contrast, humidity showed a positive correlation with infestation frequency, indicating that higher humidity levels increase fungal infestation (Spearman’s correlation = 0.12, p ≤ 0.05).